Community empowerment through diversification of processed products made from cassava in the Sasa sub-district, Ternate city - Faisal Yahya Habsyi; Datje Renjaan; Iswadi Ahmad (Universitas Muhammadiyah Magelang, 2022)
In North Maluku, cassava has long been used as a substitute to rice. Cassava is processed into sago kasbi and pupeda as well as sago trees, which are traditional staple foods. Products made from processed cassava are white, while those made from processed sago palms are brown. The limited knowledge of the community in the processing of cassava-based food ingredients causes the processed products produced to be not varied and do not provide added value economically. This encourages community service program in Sasa Village with the baseline method, advocacy and training as well as monitoring and evaluation. The success rate of training in making sago kasbi with orange and chocolate flavors is above 90% or in the very good category. This demonstrates that the trainees comprehend the information provided and are able to put it into practice when making sago kasbi.